Successful Treatment of Transplant Associated Thrombotic Microangiopathy (TA-TMA) with Low Dose Defibrotide - Devadas, Santhosh Kumar (Indian J Hematol Blood Transfus, 2017)
Transplant associated microangiopathy (TA-TMA) is a potentially serious complication of stem cell transplantation. Though stopping calcineurin/mTOR inhibitor is the first step in managing TA-TMA, this is not always adequate. The pathophysiology of TA-TMA is different from microangiopathy seen in other settings. Many drugs have been used in TA-TMA with modest responses. Defibrotide has been explored in TA-TMA in the past with good results. However, its availability is erratic and cost of therapy very high. Hence its routine use in low middle income country (LMIC) is financially demanding. We report the use of low dose defibrotide safely and successfully in this case series. This is pertinent more to LMIC’s and warrants prospective evaluation.